2022
DOI: 10.1186/s12909-022-03351-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of virtual training by serious game and lecture on operating room novices’ knowledge and performance about surgical instruments setup: a multi-center, two-arm study

Abstract: Background Game-based training is increasingly implemented in different nursing fields, as it allows students to learn experientially, with the flexibility to regulate their training based on their personal progresses and abilities. This study aimed to compare the effects of virtual training by the “Playing with Surgical Instruments (PlaSurIn)” game and the lecture on the surgical instruments setup knowledge and performance of Operating Room (OR) novices. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…In the semi-experimental study of Akbari et al ( 2021), the results showed the average knowledge scores of surgical technology students in the intervention group (teaching surgical table arrangement using games). (6.70 ± 0.72) were significantly higher than the control group (teaching surgical table arrangement using the speech method was (5.90 ± 1.71) (P = 0.040) [68].…”
Section: Discussionmentioning
confidence: 75%
“…In the semi-experimental study of Akbari et al ( 2021), the results showed the average knowledge scores of surgical technology students in the intervention group (teaching surgical table arrangement using games). (6.70 ± 0.72) were significantly higher than the control group (teaching surgical table arrangement using the speech method was (5.90 ± 1.71) (P = 0.040) [68].…”
Section: Discussionmentioning
confidence: 75%
“…This, coupled with engaging and positive learning experiences, reduces reliance on educational resources and fosters active, independent learning—especially when conventional training methods are inaccessible. This approach helps in sustaining knowledge levels, preventing decay over time, and attaining learning outcomes equivalent to traditional education forms [ 45 ]. Despite these benefits, serious games’ applications for CPR training face challenges, presenting a mixed landscape concerning usability and enjoyment quality.…”
Section: Discussionmentioning
confidence: 99%
“…This game was validated in Morteza Nasiri’s study, the English version was tuned in two successive steps, and the final round, “Playing with Surgical Instruments (PlaSurIn)”, was developed [ 34 ]. Recently, the effectiveness of the PlaSurIn game was studied by operating room students, and it was found that the knowledge and performance of operating room novices improved with this game [ 35 ]. It is worth noting that the present study had the following advantages: (1) It used a framework that the authors had proposed as a basis for developing the game.…”
Section: Discussionmentioning
confidence: 99%